DAMPAK PROGRAM PEMBINAAN KELUARGA REMAJA (BKR) TERHADAP UPAYA PENCEGAHAN STUNTING DI BALAI PENYULUHAN KB PALANGGA - Ria Harjunia; Sri Susanty; Jafriati Jafriati (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2025)
Background: Stunting is an abnormal growth condition that has become one of the primary nutritional issues among toddlers in society. The Adolescent Family Development Program (Bina Keluarga Remaja or BKR) is an initiative developed by the National Population and Family Planning Agency (BKKBN) aimed at fostering family resilience and enhancing the quality of adolescents. Purpose: This study aims to analyze the impact of the Adolescent Family Development Program (Bina Keluarga Remaja or BKR) on stunting prevention within the operational area of the Family Planning Counseling Center in South Palangga District. Methods: This research employs a quantitative method with a pre-experimental approach, conducted from May to June 2024. The study population consists of 350 adolescents attending junior high schools (SMP) and vocational high schools (SMK) in the Amondo Village area. The sample was selected using simple random sampling, resulting in a total of 188 participants, comprising 94 junior high school students and 94 vocational high school students. Results: The research results indicate a p-value of 0.000 for the knowledge variable, a p-value of 0.000 for the attitude variable, and a p-value of 0.000 for the action variable. Conclusion: The Adolescent Family Development Program significantly influences adolescents' knowledge, attitudes, and actions in preventing stunting. Collaboration is essential, involving adolescents' participation, parents' skills in guiding their teenagers, school-level supervision, government policy support, and the competencies of educators and counselors in providing education and monitoring.